2010
DOI: 10.1038/msb.2010.90
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell quantification of IL‐2 response by effector and regulatory T cells reveals critical plasticity in immune response

Abstract: The sensitivity of T cells to interleukin-2 (IL-2) can vary by three orders of magnitude and is determined by the surface densities of the IL-2 receptor α subunits.Regulatory T cells inflict a double hit on effector T cells by lowering the bulk IL-2 concentration as well as the sensitivity of effector T cells to this crucial cytokine.This double hit deprives weakly activated effector T cells of pSTAT5 survival signals while having only minimal effects on strongly activated effector cells that express increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
290
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(314 citation statements)
references
References 62 publications
15
290
1
2
Order By: Relevance
“…For example, membrane leakage and spiking threshold are set to make neurons respond only to a critical level of synaptic inputs [33]. Similar mechanisms have been observed at the cellular as well as cellular network scales [34][35][36][37]. Our results expose a mechanism by which reliable stimuli may overcome the activation threshold and be amplified even if they are carried by only a single member of the group.…”
Section: Discussionsupporting
confidence: 69%
“…For example, membrane leakage and spiking threshold are set to make neurons respond only to a critical level of synaptic inputs [33]. Similar mechanisms have been observed at the cellular as well as cellular network scales [34][35][36][37]. Our results expose a mechanism by which reliable stimuli may overcome the activation threshold and be amplified even if they are carried by only a single member of the group.…”
Section: Discussionsupporting
confidence: 69%
“…For example, the activation of individual T cells does not occur homogeneously upon stimulation-even isogenic ones-but rather activate in a digital (on/off) manner, resulting from variations in transcriptional activity or gene accessibility (25,26), the numbers and dynamic expression of signaling receptors (e.g., CD8, IL-2R), and regulators of both positive and negative feedback loops (e.g., ERK, SHP-1, and RAS) (23,30,38,39). Expression of IL-2 and IFN-γ in human CD4 + T cells has also been shown to depend on the categorical translocation of the transcription factor NFATc2 (24).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of an immunotherapy depends upon its ability to effectively overcome immune evasion mechanisms and generate new antitumor responses and/or upregulate the existing responses. Feinerman et al 45 suggested a tug-of-war hypothesis, in which there is competition for IL-2 between Tregs and Teff cells. Although our study used the down-regulation of IL-2 as an indicator of Treg function, it is unclear whether IL-2 is the primary molecular target of suppression.…”
Section: Western Blot Analysismentioning
confidence: 99%